2021
DOI: 10.3390/pathogens10111480
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CTX-M Type ESBL E. coli from Sheep and Their Abattoir Environment Using Whole-Genome Sequencing

Abstract: Widespread dissemination of extended-spectrum beta-lactamase (ESBL) Escherichia coli (E. coli) in animals, retail meats, and patients has been reported worldwide except for limited information on small ruminants. Our study focused on the genotypic characterization of ESBL E. coli from healthy sheep and their abattoir environment in North Carolina, USA. A total of 113 ESBL E. coli isolates from sheep (n = 65) and their abattoir environment (n = 48) were subjected to whole-genome sequencing (WGS). Bioinformatics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
2
1
Order By: Relevance
“…pneumonia [26], Achromobacter xylosoxidan [27], Escherichia. coli [28], Acinetobacter pittii [29] and E. cloacae [30] in a variety of countries, however, was quite rare in our study. Which may be related Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…pneumonia [26], Achromobacter xylosoxidan [27], Escherichia. coli [28], Acinetobacter pittii [29] and E. cloacae [30] in a variety of countries, however, was quite rare in our study. Which may be related Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…ST93, ST206, and ST1276 each appeared in 2 isolates, whereas the remaining ST types were represented by only one isolate ( Table 4 ). Based on our literature search, it was found that 9 of these ST types have been associated with bla CTX-M-55 previously (ST10, ST38, ST48, ST93, ST156, ST162, ST224, ST1011, ST2011) ( Zhang et al, 2014 ; Zurfluh et al, 2015 ; Miao et al, 2017 ; Atlaw et al, 2021 ; Chenouf et al, 2021 ; Li et al, 2021 ; Nittayasut et al, 2021 ; Shin et al, 2021 ; Truong et al, 2021 ; Chotinantakul et al, 2022 ; Dos Anjos Adur et al, 2022 ; Soncini et al, 2022 ). The remaining 18 ST types, comprising 25 E. coli strains, were found to be associated with bla CTX-M-55 for the first time, with ST6707 being detected in 6 stains.…”
Section: Resultsmentioning
confidence: 99%
“…While the selection of AMR is often associated with hospital antibiotic use, many animal reservoirs now exist. There are several reports of drug-resistant Enterobacteriaceae in various livestock, including poultry, sheep, cattle, and pigs [7][8][9][10]. Furthermore, despite the lack of prior antibiotic exposure in wildlife, AMR has been reported in monkey [11], green sea turtles [12], and black rhinoceros [13], probably due to exposure to antibiotic-resistant organisms at the human-animal-environment interface.…”
Section: Introductionmentioning
confidence: 99%